IL‐25 exhibits disparate roles during Th2‐cell differentiation versus effector function. Issue 7 (19th May 2014) - Mearns, Helen; Forbes‐Blom, Elizabeth. E.; Camberis, Mali; Tang, Shiau‐Choot; Kyle, Ryan; Harvie, Marina; Kleinschek, Melanie A.; Gros, Graham Le
<x xml:space="preserve">Abstract</x> A keenly sought therapeutic approach for the treatment of allergic disease is the identification and neutralization of the cytokine that regulates the differentiation of T helper 2 (Th2) cells. Th2 cells are exciting targets for asthma therapies. Recently, the cytokine IL‐25 has been shown to enhance Th2‐type immune activity and play important roles in mediating allergic inflammatory responses. To investigate this further, we crossed IL‐25−/− C57BL/6 mice with G4 IL‐4 C57BL/6 reporter mice and developed an assay for in vitro and in vivo IL‐4‐independent Th2‐cell differentiation. These assays were used to determine whether IL‐25 was critical for the formation of Th2 cells. We found there was no physiological role for IL‐25 in either the differentiation of Th2 cells or their development to effector or memory Th2‐cell subsets. Importantly, this data challenges the newly found and growing status of the cytokine IL‐25 and its proposed role in promoting Th2‐cell responses.